Genetic diversity and genotyping of Echinococcus multilocularis: a minireview - Rachel, Franziska; Conraths, Franz Josef; Maksimov, Pavlo (Frontiers in Parasitology, 2025)
The genome of Echinococcus multilocularis, one of the most dangerous endoparasites for humans in the northern hemisphere, has been studied for decades, but its global genetic diversity has not yet been fully deciphered. Yet, our understanding of the diversity of this parasite has recently improved significantly due to the development of new genotyping methods. However, the use of different methods and markers has made it difficult—and in some cases impossible—to compare existing studies directly. As a result, accurate information on the global genetic diversity of E. multilocularis remains unavailable, although such knowledge is essential from both clinical and epidemiological perspectives. Here we provide an overview of the state of knowledge on the genetic diversity of E. multilocularis, and the methods used for genotyping this parasite and provide an outlook on needed future research to understand the diversity of this fascinating parasite.